Pengaruh Ketidakmayoritasan Partai Politik Kepala Daerah di DPRD (Divided Government) terhadap Keterlambatan Penetapan APBD - Kartiko, Sigit Wahyu (UI Scholars Hub, 2012)
Why is APBD (Regional Budget) often enacted after the budgeted financial year has started? Is it because of political factor? The research would like to highlight the economic and political perspectives of divided government as one of the factors of the bad performance of the Regional Budget (APBD) enactment. By using logit regression equation model, a result obtained shows that government formations from Legislative General Elections 2004 and Direct Local Elections of the years 2005, 2006, and 2007, such as single minority party, minority coalition, majority coalition, and single majority party, influence the regional late budget of the year 2008-2009.